Markov Chain Model of Neuropathy Progression of Type 2 Diabetes: A Case Study in Bono East Region - Bayeldeng, Gladys (University of Cape Coast, 2025)
Type 2 diabetes mellitus (T2DM) is a chronic non-communicable disease that causes damage to the kidneys, heart, nerves, and blood vessels. In recent times, there has been a surge in T2DM cases, and it has been associated with overweight, obesity, lack of adequate physical activity, gender, urbanisation, and the educational level of people. The study modelled the neuropathy progression of T2DM in patients using the Markov Chain model. The fasting blood sugar (FBS) levels of patients and neuropathy conditions developed during the time of this study were classified into eight states: State 1 (low FBS level), State 2 (normal FBS level), State 3 (moderate FBS level), State 4 (high FBS level), State 5 (numbness), State 6 (ulcers), State 7 (amputation), and State 8 (death). The study found that females were more exposed to the disease than their male counterparts, and 96% of the patients were hypertensive. Most patients fall within the age bracket of 40-60 years. Patients in the long term have a high risk of their conditions deteriorating rather than improving. Patients who have low FBS levels have a 50% chance of dying within the year, and patients in the ulcer state have two options: they either remain in the same condition or progress to the next state, which is the amputation state. Patients in the low FBS state have a mean sojourn time of 14 years, while patients in the normal and moderate states have a mean sojourn time of 27 years each. Patients in high and numbness states have mean sojourn times of 26 and 23, respectively. However, patients in an ulcer state have a mean sojourn time of two years before they enter the absorbed states. The study therefore recommends intense public education on the factors associated with diabetes, the risk of progression of T2DM, and prevention measures.
xii, 97p:, ill
Keywords: Absorbed States; Hyperglycaemia; Hypoglycaemia; Neuropathy; Retinopathy; Transient States